MODERN ARCHITECTURE IN IRON-PLACE CONCRETE STRUCTURES - Sotvoldiyev Azamat (American Journals Publishing, 2024)
This article is about the role of reinforced concrete structures in modern architecture, and the advantages of reinforced concrete structures speak about their capabilities
Keywords: Modern architecture, reinforced concrete structures. strength, steel, skyscrapers, industrial buildings, flexibility.